Pengaturan Private Military Contractors Dalam Perang Un-Conventional Dan Implikasinya Terhadap Tanggung Jawab Negara - Johannes, Helmi Ishak; Anwar, Arman; Peilouw, Johanis Steny Franco (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Private Military Contractors, abbreviated as PMCs, are companies or corporations that provide services and expertise related to the military or similar fields.Purposes of the Research: This writing aims to understand and know the arrangement of private military contractors in unconventional wars. Methods of the Research: The research method in this paper uses a prescriptive analytical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: Conventional warfare is used to reduce the opponent's military capabilities directly through attacks and maneuvers, non-conventional warfare is an attempt to achieve victory indirectly through proxy forces. UW contrasts with conventional warfare where power is often disguised or poorly defined and relies heavily on subversion and guerrilla warfare. State responsibility is a fundamental principle in international law which originates from the doctrines of international jurists. State responsibility arises when there is a violation of international obligations to do something, both obligations based on international agreements and based on international customs.